2007
DOI: 10.1002/bem.20322
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosome behaviour is unaffected by weak pulsed electromagnetic fields

Abstract: The present study examined the effect on rat cortical synaptosomes of a 2 h exposure to 50-Hz electromagnetic fields (EMFs) with a peak magnetic field of 2 mT. We measured modifications of synaptosomal mitochondrial respiration rate, ATP production, membrane potential, intrasynaptosomal Ca(2+) concentration and free iron release. The O(2) consumption remained unvaried in exposed synaptosomes at about 2 nM O(2)/min/mg proteins; ATP production was also unchanged. The intrasynaptosomal Ca(2+) concentration decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Similarly, the results of our study demonstrated that ELF-EMF (100mT/1 Hz for 5 days, 120 min each day) causes in vitro apoptosis in the mentioned cell line (Figure 1). In 2007, Aldinucci also observed increased induction of apoptosis in human cancer cells after exposure to radiation of 50 Hz EMF magnetic field of 1 mT [32]. Similar results were obtained in a study on the MCF-7 cell line and the normal MCF-10 cell line at 20 Hz; using an EMF of 2,3,5 mT for 60 minutes [33].…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, the results of our study demonstrated that ELF-EMF (100mT/1 Hz for 5 days, 120 min each day) causes in vitro apoptosis in the mentioned cell line (Figure 1). In 2007, Aldinucci also observed increased induction of apoptosis in human cancer cells after exposure to radiation of 50 Hz EMF magnetic field of 1 mT [32]. Similar results were obtained in a study on the MCF-7 cell line and the normal MCF-10 cell line at 20 Hz; using an EMF of 2,3,5 mT for 60 minutes [33].…”
Section: Discussionsupporting
confidence: 63%